Influence of minimalist footwear on running performance and injury - Andreyo, E.; Unverzagt, C.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2022)
Runners and clinicians have long sought to enhance distance running performance and reduce the occurrence of running-related injuries. Footwear selection often comes to the forefront in such pursuits, yet remains a common source of controversy in the literature and practice. In particular, the utilization of minimalist footwear has fluctuated in popularity over the last several decades, with some proponents suggesting that it can promote improvements in running economy and reduce injury rates. However, a closer look at the literature shows anything but straightforward and consistent recommendations. The purpose of this article is to outline the effects of minimalist footwear on running performance and injury, with a focus on its associated impact on running mechanics. The authors also aim to identify who may be the ideal client to transition to minimalist running and how to minimize the risk of injury during the transition.